Use of fentanyl in adolescents with clinically severe obesity undergoing bariatric surgery: a pilot study - Vaughns, Janelle D.; Ziesenitz, Victoria C.; Skopp, Gisela; Weiß, Johanna; Mikus, Gerd (Pediatric drugs, 2017)
BackgroundThe number of obese pediatric patients requiring anesthesia is rapidly increasing. Although fentanyl is a commonly used narcotic during surgery, there are no pharmacokinetic (PK) data available for optimal dosing of fentanyl in adolescents with clinically severe obesity.Materials and MethodsAn institutional review board-approved exploratory pilot study was conducted in six adolescents aged 14-19 years undergoing bariatric surgery. Mean total body weight (TBW) and mean BMI were 137.4 ± 14.3 kg and 49.6 ± 6.4 kg/m2 (99.5th BMI percentile), respectively. Fentanyl was administered intravenously for intraoperative analgesia based on ideal body weight per standard of care. PK blood samples were drawn over a 24-h post-dose period. Fentanyl PK parameters were calculated by non-compartmental analysis.ResultsMean fentanyl AUC0-∞ was 1.5 ± 0.5 h·ng/mL. Systemic clearance of fentanyl was 1522 ± 310 mL/min and 11.2 ± 2.6 mL/min·kg TBW. Volume of distribution was 635 ± 282 L and 4.7 ± 2.1 L/kg TBW. While absolute clearance was increased, absolute volume of distribution was comparable to previously established adult values.ConclusionsThese results suggest that fentanyl clearance is enhanced in adolescents with clinically severe obesity while volume of distribution is comparable to previously published studies.Study registrationNCT01955993 (clinicaltrials.gov).